The taboo of death in nursing homes: Reflections on the pandemic - Usero Liso, Luis Manuel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Death taboo in some nursing homes produces the elimination of rites and mourning. However, from the taboo practices will lead new funerary rituals. The pandemic will exacerbate such practices.